'Ain't I also a migrant?' An ethnodrama of weaving knowledges otherwise in Finnish migration research. Issue 3 (2nd September 2021) - Țîștea, Ioana
ABSTRACT: Previous Nordic migration and minority studies focus little on who produces research about migration and migrant education and in what ways. In contrast, by inquiring into how migrants and researchers themselves as knowing subjects are constituted through research and educational practices, this article seeks to destabilize established modes of knowing and of performing research. Through ethnodrama, it explores the effects of performing abilities to pass as non/not-quite/white, and the related abilities to pass as a knowing subject or not. This enables enquiring what counts as valid knowledges and ways of knowing, and who is considered a legitimate knowing subject in migrant educational and research settings and practices in Finland. This study joins a growing body of auto/ethnographic research exploring Eastern European proximities-to/distances-from whiteness in the Nordic space, through embodiment and discomfort with established ways of knowing. The ethnodrama brings into dialogue discussions on (epistemic) racism and (contested) whiteness with current controversies on racialized researcher positionality in feminist circles.